A STUDY ON TEACHING COMPETENCY OF SECONDARY SCHOOL TEACHERS - Das, Sijila; M, Nalinilatha (International Journal of Research -GRANTHAALAYAH, 2017)
The role of teacher is proficient, be composed of academic, didactic and social roles. Academic roles cover teaching, instructing and supervisory characters and pedagogical characters include instructional, valuation and simplifying roles. The study aimed to identify the teaching competency of secondary school teachers. The investigator adopted survey method to study the teaching competency between teachers from selected government, private and aided school. For this study a sample of 300 school teachers from eight various schools which are situated in Palakkad district selected by the investigator using simple random sampling technique. The findings revealed that there is no significant difference towards teaching competency among selected secondary school teachers with respect to personal variables like Gender, Marital Status, Educational Qualification, Type of Management and Teaching experience. The findings of the study help to discover the teaching competency of secondary school teachers in the society.